2020
DOI: 10.1088/1748-9326/aba716
|View full text |Cite
|
Sign up to set email alerts
|

Real-world insights on public charging demand and infrastructure use from electric vehicles

Abstract: The city of Berlin has significantly expanded public charging infrastructure for electric vehicles. As a result of this investment, real-world charging data for the city of Berlin are available for the first time. In addition to other metrics, this dataset contains specific information about carsharing vehicles. This research letter offers numerous insights into public charging demand and infrastructure. The results are only now available due to a sufficient fleet size of electric vehicles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…The distributions in figures 5(a) and (b) show utilization times ranging from a few minutes to more than 48 h. One reason for this range of utilization times could be the use of charging stations as short-and even long-term parking places. The phenomenon of charging stations being used in this way has also been documented in other studies (Hardinghaus et al 2020, Hecht et al 2020. The ANOVA shows a statistically significant relationship between utilization time and population density (F-value = 2.01, p-value = 0.0363).…”
Section: Spatial and Temporal Utilization Patternssupporting
confidence: 71%
See 2 more Smart Citations
“…The distributions in figures 5(a) and (b) show utilization times ranging from a few minutes to more than 48 h. One reason for this range of utilization times could be the use of charging stations as short-and even long-term parking places. The phenomenon of charging stations being used in this way has also been documented in other studies (Hardinghaus et al 2020, Hecht et al 2020. The ANOVA shows a statistically significant relationship between utilization time and population density (F-value = 2.01, p-value = 0.0363).…”
Section: Spatial and Temporal Utilization Patternssupporting
confidence: 71%
“…Indirect data is often used instead of real-world data from charging stations to determine the demand for charging infrastructure. Hardinghaus et al (2020) identified four data sources for such studies: (1.) GPS (global position system) data from vehicles, (2.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to NHTS datasets for estimating charging is datasets on EV charging from public and private charging stations (Hardinghaus et al, 2020;Zachary et al, 2019;Kezunovic et al, 2020;Huber et al, 2020;Almaghrebi et al, 2020;Noussan and Neirotti, 2020). Using data from public charging points in Berlin, Hardinghaus et al (2020) found the utilization of charging points to be similar even though the charging points were distributed unequally in the city. Investigating emissions from EVs and using data from public and private chargers in Germany, Noussan and Neirotti (2020) found that the influence of charging strategy had a limited impact on emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose was to minimize costs of the CS and to provide an efficient model. A research 42 presents the CSs for EVs in Berlin. Their results show that the CSs' distribution is unequal because of the uneven charging demand.…”
Section: Overview Of Main Concepts and Technologiesmentioning
confidence: 99%